Evaluation The Effects of Platelet Activating Factor (PAF) on Immunothrombosis in Severe and Critical COVID-19 Infections Compared to Mild Cases - Muhammed, Abdul Q. W. (Scientific Journal of Medical Research, 2022)
Back ground: The study aimed to evaluate the correlation between the platelet activating factor (PAF) and immunothrombosis in severe and critical COVID-19 patients in comparison with mild cases. Materials and Methods: A cross sectional study was conducted. From October 1 2021 to May 30 2022, a total of 82 COVID-19 patients were recruited at AL-Hussein Medical City in Kerbala, consisting of 44 males and 38 females, and their ages ranged from 25 to 85 years old. All participants were hospitalized after testing positive for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). 27 were diagnosed with mild COVID-19 and 27 with severe cases, while 28 patients had acute diseases. Results: In mild COVID-19 cases, PAF levels increased very quickly, but in severe and critical cases PAF levels stabilized within a limited range (p = 0.447). Conclusion: Platelet-activating factor PAF increased in mild cases, but then it stabilized within a limited range in severe and critical COVID-19 cases.